The first occurrence of the cyanobacterial alkaloid toxin cylindrospermopsin in the Czech Republic as determined by immunochemical and LC/MS methods - Bláhová, Lucie; Oravec, Michal; Marsálek, Blahoslav; Sejnohová, Lenka; Simek, Zdenek; Bláha, Ludek (Toxicon, 2009)
Cylindrospermopsin (CYN) is a newly emerging carcinogenic alkaloid originally identified in tropical cyanobacteria Cylindrospermopsis raciborskii. Some recent studies reported production of this toxin also by other cyanobacteria in European countries. Here we report comparison of the immunochemical ELISA determination with the liquid chromatography/mass spectrometry (LC/MS) method for CYN analyses in the samples from the Czech Republic, Central Europe. We have analysed 56 samples of raw lake waters collected from 32 localities. CYN was found at 3 localities with Aphanizomenon sp. sub-dominated water blooms. Results of the ELISA and LC/MS showed good qualitative agreement. However, concentrations determined by ELISA (0.4-4 microg/L) were systematically higher than concentrations determined by LC/MS (0.01-0.3 microg/L). Differences between methods could be attributed to matrix effects (both in ELISA and LC/MS) or ELISA cross-reactivity with other unidentified derivatives of CYN. Our study demonstrates for the first time occurrence of CYN in the Central Europe. With respect to its suspected carcinogenicity, further research on distribution, concentrations and risks of this cyanobacterial toxin is needed.
Keywords: bakteriální toxiny; toxiny kmene Cyanobacteria; Fresh Water; chromatografie kapalinová; hmotnostní spektrometrie; Mass Spectrometry; Czech Republic; Česká republika; Immunochemistry; Enzyme-Linked Immunosorbent Assay; uracil; ELISA; sladká voda; Cyanobacteria; Environmental Monitoring; monitorování životního prostředí; alkaloidy; imunochemie; Chromatography, Liquid; sinice; Alkaloids; Cyanobacteria Toxins; Uracil; Bacterial Toxins